1985
DOI: 10.1620/tjem.147.429
|View full text |Cite
|
Sign up to set email alerts
|

Determination of urine neuron-specific enolase levels in neuroblastoma patients.

Abstract: Urine levels of neuron-specific enolase were determined in 3 neuroblastoma patients (1 in an advanced state and 2 in remission), 25 control children, 37 control adults and 4 children with hematuria by means of the double-antibody inhibition radioimmunoassay specific to the y subunit of enolase isozymes. The levels of neuron-specific enolase mean +S.D. ng/ creatinine mg in an advanced neuroblastoma patient were elevated (1.25±0.29 before or after treatment and range 1.61-74.2 during treatment) when compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These results raise the possibility of serum NSF measurement as an additional and simple diagnostic method (Ishiguro et al 1982(Ishiguro et al , 1983. We also reported that urine levels of NSE were higher in an infant with advanced neuroblastoma than those in controls (Gotoh et al 1985). In this paper, we examined the correlation between urine NSF levels and clinical features in 3 patients with neuroblastoma in details.…”
mentioning
confidence: 94%
“…These results raise the possibility of serum NSF measurement as an additional and simple diagnostic method (Ishiguro et al 1982(Ishiguro et al , 1983. We also reported that urine levels of NSE were higher in an infant with advanced neuroblastoma than those in controls (Gotoh et al 1985). In this paper, we examined the correlation between urine NSF levels and clinical features in 3 patients with neuroblastoma in details.…”
mentioning
confidence: 94%